2013
DOI: 10.1002/cncr.28249
|View full text |Cite
|
Sign up to set email alerts
|

Improving the quality of bone marrow assessment

Abstract: BACKGROUND: Successful bone marrow assessment is essential to the diagnosis and staging of hematologic malignancies. The objective of this study was to determine whether specific operator techniques and/or use of a specimen preparation checklist could impact the quality of bone marrow assessment by reducing the frequency of nonspicular aspirates, small cores, and nondiagnostic samples. METHODS: All bone marrow biopsies performed at the Dana-Farber Cancer Institute from April, 2012 to September, 2012 were eligi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Textbooks and BMA guidelines rarely mention the aspiration technique, and when they do, rapid aspiration is mentioned [2,3,4]. Former studies have examined the impact that biopsy devices, operator profession and experience have on the quality of bone marrow (BM) assessment and pain [1,5,6,7,8,9,10]. To our knowledge, studies on the aspiration technique and its association with specimen quality are sparse.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Textbooks and BMA guidelines rarely mention the aspiration technique, and when they do, rapid aspiration is mentioned [2,3,4]. Former studies have examined the impact that biopsy devices, operator profession and experience have on the quality of bone marrow (BM) assessment and pain [1,5,6,7,8,9,10]. To our knowledge, studies on the aspiration technique and its association with specimen quality are sparse.…”
Section: Introductionmentioning
confidence: 99%
“…Obtaining the optimal quality of the specimen for pathologic review is obviously important [1]. Textbooks and BMA guidelines rarely mention the aspiration technique, and when they do, rapid aspiration is mentioned [2,3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Checklists covering vital points in BM sampling are useful for reminding these personnel of the points before sampling, for assistants to inform operators of the estimation of collected samples during sampling, and for providing feedback about the quality of samples to these personnel from laboratories later. 11,20 Although such checklists can help improve and generalise required knowledge, technical aspects need effective and practical training. In this regard, training for nurse practitioners and doctors supervised by wellexperienced experts is strongly recommended.…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, BM cells were aspirated from patients with various diseases, without focusing on MDS, at a single hospital (or a hospital group in one study), and it was reported that approximately 20%-30% of the aspirated BM samples were massively haemodiluted. [11][12][13] Here, we report the first study to examine the incidence of massive haemodilution in nationwide BM samples aspirated from patients who were diagnosed with or suspected of having MDS in Japan.…”
Section: O R I G I N a L P A P E R H A E M A T O L O G I C A L M A L ...mentioning
confidence: 99%
“…Furthermore, several studies have shown that there is a clear correlation between sample quality, surgeon experience, technique and needle [ 35 , 44 , 45 ]. Since the number of MSCs decreases when aspiration is repeated at the same location, it is recommended that the location of harvesting should be changed at least after every third puncture in order to obtain the highest possible yield of MSCs [ 35 ].…”
Section: Discussionmentioning
confidence: 99%